Effect of immersion in various disinfectant solutions on the properties of a heat-cured acrylic resin - Cláudia Jiménez PEREIRA; Bruna GENARI; Vicente Castelo Branco LEITUNE; Fabrício Mezzomo COLLARES; Susana Maria Werner SAMUEL (Faculdade São Leopoldo Mandic, 2019)
Objective: The aim of the present study was to evaluate the influence, of immersion in different disinfectant solutions, on microhardness and surface roughness of a heat-cured acrylic resin. Methods: Specimens were immersed in distilled water, commercial vinegar for domestic use, sodium hypochlorite and hydrogen peroxide, for 150 hours or 300 hours (n=10). After periods of immersion, Knoop microhardness and surface roughness were evaluated using a microhardness tester and a roughness tester, respectively. The data were analyzed using two-way ANOVA and Holm-Sidak, at a level of significance of 5%. Results: The microhardness values ranged from 16.90 ± 0.33 to 17.80 ± 0.51 and roughness values from 0.05 ± 0.01 to 0.08 ± 0.02. There is no difference in microhardness and roughness between groups and times (p>0.05). Conclusion: Within the limitations of this study, it is possible to conclude that vinegar and hydrogen peroxide, as alternative disinfectant solutions for acrylic resin devices, did not promote deleterious effects on microhardness and polishing of a heat-cured acrylic resin used for the fabrication of prostheses, neither in the medium term nor the long term.